2021
DOI: 10.1029/2021gl094873
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Convective Systems Dominate the Energetics of the South Asian Summer Monsoon Onset

Abstract: The onset of the South Asian summer monsoon (SASM) is marked by a rapid reversal of prevailing winds and an abrupt increase of precipitation over South Asia, which usually occurs from late May to early June

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It redistributes heat, moisture, and momentum, and produces tremendous amount of precipitation in the tropics (e.g., Chen et al., 2020; Mapes & Houze, 1993; Nesbitt et al., 2006; Schumacher & Houze, 2003). Latent heating released by tropical convection is the major driver of atmospheric general circulations, and clouds associated with tropical convection considerably modulate the global radiation balance (e.g., Chen et al., 2022; Hartmann et al., 2001; Trenberth, 2002; Webster et al., 1996; X. Chen et al., 2021). Hence, appropriately representing tropical convection in numerical models is crucial to the realistic simulation of atmospheric variability across various temporospatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…It redistributes heat, moisture, and momentum, and produces tremendous amount of precipitation in the tropics (e.g., Chen et al., 2020; Mapes & Houze, 1993; Nesbitt et al., 2006; Schumacher & Houze, 2003). Latent heating released by tropical convection is the major driver of atmospheric general circulations, and clouds associated with tropical convection considerably modulate the global radiation balance (e.g., Chen et al., 2022; Hartmann et al., 2001; Trenberth, 2002; Webster et al., 1996; X. Chen et al., 2021). Hence, appropriately representing tropical convection in numerical models is crucial to the realistic simulation of atmospheric variability across various temporospatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Tropical MCSs are not only responsible for more than 60% of the total precipitation in the Tropics (Houze, 2004; Liu, 2011; Mohr et al., 1999; Nesbitt et al., 2006; Roca & Fiolleau, 2020; X. Chen et al., 2022), but also influence global weather through convective momentum transport (Badlan et al., 2017; G. J. Zhang & McFarlane, 1995; Houze, 1973) and latent heating effects (Held & Hou, 1980; Hoskins & Karoly, 1981; Johnson & Ciesielski, 2013; Madden & Julian, 1971; Satoh, 1994; Weickmann, 1983; Wheeler & Kiladis, 1999). Furthermore, recent studies have demonstrated that tropical MCSs play important roles in the onset of monsoons and in the monsoonal overturning circulation (X. Chen, Leung, Feng, & Song, 2021; X. Chen, Leung, Feng, Song, et al., 2021; X. Chen et al., 2018a). These monsoonal roles establish the significance of tropical MCSs in the regional and global climate (i.e., beyond weather timescales).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen, X. et al. (2021) reported that mesoscale organization of deep convection plays a dominant role in positive feedbacks associated with convection, which accelerates the energy cycle of the South Asian summer monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoscale organized convection was also found to affect the mean-state and evolutions of large-scale circulations (Hartmann et al, 1984;Moncrieff, 1995). For example, Chen, X. et al (2021) reported that mesoscale organization of deep convection plays a dominant role in positive feedbacks associated with convection, which accelerates the energy cycle of the South Asian summer monsoon.…”
mentioning
confidence: 99%